The effects of krill oil administration on Inflammatory Bowel Diseases (IBDs): a promising new therapy - Tessitore, Vincenzo (Progress in Nutrition, 2017)
Recent research carried out in Norway on rats affected by experimental colitis have proved that the supplementation of high doses of krill oil in diet determined a significant improvement in some indices of inflammation. Existing few and partial similar investigation on humans triggered this trial conducted on 32 patients, who were administered high doses of krill (krill oil, no. 3 capsules of 500 mg a day for 90 days). The measurement of the trend of intestinal inflammation in each patient was checked every 30 days for 90 days through faecal immunochromatography of calprotectin, which at present, as it is well known, is the gold faecal biomarker of the evolution of intestinal inflammation. The results obtained show that 25 patients out of 32 experienced a clinical reduction of the symptoms and normalization of the values of faecal calprotectin. These results justify the use krill oil in IBD.